PENGARUH KEPERCAYAAN, PROMOSI, DAN ULASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK AKOMODASI DI APLIKASI TRAVELOKA - Stepanus Dwi Nugroho Adi; Audita Nuvriasari (Departemen Manajemen, 2021)
This study aims to analyze the impact of trust, promotion, and product reviews on purchase decision of product accomodation on the Traveloka application. The research using a quantitative approach. Primary data collected by distributing the questionnaires to a sample of 100 Traveloka customers who are at least 17 years old, live in Java island, and purchase accommodation products on the Traveloka application from November 2019 to October 2020. This study using multiple linear regression test for the data analysis. The results of this research showed that partially trust, promotion, and product reviews had a positive and significant effect on purchasing decisions. Trust, promotion, and product reviews simultaneously have a positive and significant effect on purchasing decisions. The determination test showed that the percentage of influence on trust, promotion, and product reviews is 0.514 or 51.40%, while the rest is 48.60% influenced by other variables outside this study. Trust is the most dominant or influential variable with the largest beta coefficient (β1), which is 0.408.Accommodation providers on Traveloka Apps or Traveloka management must be able to increase consumer trust, has an effective and targeted promotional strategies, and also maintain the quality of accommodation products to get positive product reviews.